Eksplorasi Hypothetical Learning Trajectory Berbasis RME pada Pembelajaran Pecahan Sekolah Dasar - Melsya Reyuni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study was motivated by persistent difficulties in learning fractions in elementary school, where students tend to rely on procedural calculation without developing conceptual understanding and mathematical representation skills. The research aimed to explore a Hypothetical Learning Trajectory based on Realistic Mathematics Education for fifth- grade students on fraction topics, particularly equivalent fractions, addition, and subtraction with different denominators. The study employed a design research approach consisting of three phases: preliminary design, teaching experiment, and retrospective analysis. The participants were six fifth-grade students from an elementary laboratory school who were grouped heterogeneously. Data were collected through classroom observations, student interviews, documentation, and analysis of student worksheets. Data analysis was conducted by comparing the predicted learning trajectory with the Actual Learning Trajectory that emerged during instruction. The findings indicate that the designed learning trajectory effectively supported students’ progression from informal understanding to formal reasoning. Contextual activities and visual strategies facilitated students’ comprehension of fraction concepts and enhanced their ability to represent mathematical ideas. Group interaction also played a crucial role in providing learning support. These results highlight the importance of carefully designed learning trajectories in fostering meaningful fraction learning.